Trapped identity in the novels of Dan Jacobson - Bekker, Janine (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1981)
Dan Jacobson has written short stories, many non-fiction articles and eight novels: The Trap (1955), A Dance in The Sun (1956), The Price of Diamonds (1957), The Evidence of Love (1959), The Beginners (1966), The Rape of Tamar (1970), The Wonder-Worker (1973), and Â· The Confessions of Josef Baisz (1977) . The first five are all set in South Africa, though Jacobson has been living in England since 1954, i.e. since before his first novel was published. A distinct break in terms of subject matter and voice occurs after The Beginners , giving Jacobson what he calls "two rounds as a novelist. But critics recognizing this break seem not to have recognized that all eight novels are linked by certain thematic preoccupations, notably the notion of the trapped identity, which this thesis will attempt to demonstrate. On a first reading of Jacobson's work one is drawn to affirm his portrayal of the position of the white English-speaking South African, but a closer reading reveals that he does not speak as vitally to the South African situation as he seems to, or has been taken to do. Why this should be so is the second main concern of this thesis. In the first chapter the expectations underlying English literary activity in South Africa are outlined, as this is a necessary background to the discussion of Jacobson's South African novels. (Introduction, p. 4)
Keywords: Jacobson, Dan -- Criticism and interpretation; Identity (Philosophical concept) in literature